Review article: does intra-arterial heparin flushing (iahf) can actually increase manual muscle test (mmt) score in chronic ischemic stroke patients? - Machfoed, Moh Hasan; Kurniawan, Mohammad; Usman, Fritz Sumantri (Folia Medica Indonesiana, 2017)
Stroke is still a major health problem in the world. Ischemic stroke accounts for 87% of all acute stroke occurrences. In 2013, the American Heart Association (AHA)/American Stroke Association (ASA), published a Guideline for the Early Management of Patients with Acute Ischemic Stroke. The managements consist of the use of recombinant tissue plasminogen activator (rtPA), endovascular treatment, etc. Unlike acute ischemic stroke, until now, no guidelines have been provided about the management of chronic ischemic stroke that approved universally. The result of the study with the title of